Using an open-source IEEE 802.21 implementation for network-based localized mobility management - Corujo, Daniel (2011)
Taking advantage of the multimode ability of modern mobile terminals, cellular operators are investing in alternate access networks (e.g., IEEE802.11 and IEEE802.16) to complement the increasingly overloaded cellular accesses. Complementing this, IP mobility support is gradually being introduced into network architectures, providing session continuity. To facilitate and optimize handover procedures between different access technologies in a seamless way, the IEEE 802.21 Media Independent Handover Services standard provides technology agnostic mechanisms to obtain information and control link layers. Implementations of the standard are appearing, but since support of IEEE 802.21 primitives directly at the link driver level is not yet realized, they have to revert to proprietary wrapping mechanisms or use specific operating system solutions to circumvent this issue. In this article we present ODTONE, an IEEE 802.21 implementation that is operating-system-independent and open source, and offers a novel approach to interfacing with different link layers that facilitates the deployment of IEEE 802.21 mobility mechanisms in multiple scenarios. We present a scenario where we integrate our middleware with an IP mobility management protocol, Proxy MIP IPv6, highlighting ODTONE¿s supporting features and impact while providing an open handover control architecture for network- based localized mobility management.